Business Management Training for the MSME / UMKM (Micro, Small and Medium Enterprises) Community in South Jakarta - Lutfi Baradja; Ice Nasyrah Noor; aina zahra parinduri (Comment: an International Journal of Community Development, 2019)
Community service (PKM) in the form of business management training and calculation of cost production is administered to the South Jakarta MSME community, which provided positive feedback. The training discussed the search for business ideas to be carried out by the MSME and to assist the community in understanding the direction and purpose of establishing a business. The training was provided to determine the vision, mission, strengths, weaknesses, opportunities, threats, and the best strategy in business management. The result of this study showed that MSME is provided training to analyze SWOT till the right strategies are formed and are guided by Instructors. Furthermore, its understanding increased with the provision of hands-on training, which provided them with a better understanding of their business objectives.